Combustible costs! Financial implications of flammable cladding for homeowners. Issue 2 (3rd April 2022) - Oswald, David; Moore, Trivess; Lockrey, Simon
Abstract: More than 3400 residential apartment buildings around Australia have flammable cladding. The costs to rectify this defect fall onto homeowners. However, there is limited information about what the costs and implications are for homeowners. This paper identifies through interviews of 16 affected homeowners from Australia the different financial costs involved in rectifying flammable cladding. A range of financial implications were revealed including: increasing levies, body corporation fees, insurance rates, council rates, legal fees, material testing, inspections, other fire strategy defects and extra fire engines responding to alarms. Future costs included fines for non-compliance, loss of property value and the rectification work. The quoted costs of rectification work ranged from A30, 000 to A12, 000, 000, depending on the scope of works required but this does not factor in those broader costs identified. The costs associated with cladding rectification have created significant financial burdens for households and influenced life decisions related to finances. The identification of the different types of costs could be used as a framework to quantify the costs to homeowners in further research. This would measure the costs as cladding rectification works are undertaken, in order to provide improved support to these households, not only in Australia but other impacted locations.